2021
DOI: 10.1016/j.jcat.2021.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Beyond confinement effects in Fischer-Tropsch Co/CNT catalysts

Abstract: Fischer-Tropsch catalyst preparation parameters, such as cobalt precursor and impregnation solvent, determine structure and in fine catalytic performances of Co-based catalysts. Co particles of 3-7 nm mean size were prepared by incipient wetness impregnation on surface-oxidized CNT. In this work the crucial impact of the chemistry operating between the Co precursor and the support during catalyst preparation on the catalyst properties is demonstrated and the influence of CNT surface chemistry on catalyst chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 101 publications
0
23
0
Order By: Relevance
“…Analysis was investigated using a monochromatized Al K α source on a ThermoScientific K α [30] . The X‐ray spot size varies from 30 to 400 μm.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis was investigated using a monochromatized Al K α source on a ThermoScientific K α [30] . The X‐ray spot size varies from 30 to 400 μm.…”
Section: Methodsmentioning
confidence: 99%
“…According to the heteroatom doping, different types of surface groups have been reported to facilitate the H-spillover on Pd catalysts, such as N-quaternary atoms for N-doped materials [65] and quinone groups for O-doped ones. [67] Interestingly, it was also reported that water molecules, present as solvent during 4-NP reduction, significantly facilitate the H-spillover reaction on carbon supports by acting as shuttle/stabilizer for the Hspecies. [63,65,68] H-spillover should not occur on undoped CNTs because of the low concentration of surface oxygen groups.…”
Section: Chemcatchemmentioning
confidence: 99%
“…For this set of samples, we first confirmed that the nitrate metal precursor did not cause any reoxidation of the carbon surface during catalyst synthesis (Table S4). Such a reoxidation was observed for Co/CNT catalysts, albeit for much higher metal loadings . The combined XPS/UPS analysis of the Pd­(NO 3 ) 2 /CNT precursor showed a rapid drop of the O/C ratio from 0.21 to 0.12 when heating the sample to 200 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Such a reoxidation was observed for Co/CNT catalysts, albeit for much higher metal loadings. 64 The combined XPS/UPS analysis of the Pd(NO 3 ) 2 /CNT precursor showed a rapid drop of the O/C ratio from 0.21 to 0.12 when heating the sample to 200 °C. The latter is close to the O/C ratio of 0.11 obtained for the oxidized CNTs when defunctionalized at the same temperature.…”
Section: Theoretical Insights Intomentioning
confidence: 99%